2021
DOI: 10.1177/01461672211053453
|View full text |Cite
|
Sign up to set email alerts
|

Do Grittier People Have Greater Subjective Well-Being? A Meta-Analysis

Abstract: The present study conducted a meta-analysis to examine the relation between grit and subjective well-being (SWB). The association between grit (i.e., overall grit, perseverance of effort, and consistency of interest) and SWB (i.e., positive affect, negative affect, happiness, depression, life satisfaction, job satisfaction, and school satisfaction) were synthesized across 83 studies and 66,518 participants. The results based on a random-effects model showed a substantial correlation between overall grit and SW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 141 publications
0
13
0
1
Order By: Relevance
“…Positive personality traits are motivation to promote job satisfaction ( Sinniah et al, 2022 ), and grit as a personality strength affects people’s subjective well-being and is a significant predictor of job satisfaction in particular ( Goodman et al, 2017 ). A meta-analysis ( Hou et al, 2022 ) has shown that grit was positively associated with job satisfaction, suggesting that more extraordinary grit was associated with greater job satisfaction. A study ( Dugan et al, 2019 ) of US salespeople also has shown a significant relationship between grit and job satisfaction, with gritty salespeople performing better and having higher job satisfaction than their less gritty counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Positive personality traits are motivation to promote job satisfaction ( Sinniah et al, 2022 ), and grit as a personality strength affects people’s subjective well-being and is a significant predictor of job satisfaction in particular ( Goodman et al, 2017 ). A meta-analysis ( Hou et al, 2022 ) has shown that grit was positively associated with job satisfaction, suggesting that more extraordinary grit was associated with greater job satisfaction. A study ( Dugan et al, 2019 ) of US salespeople also has shown a significant relationship between grit and job satisfaction, with gritty salespeople performing better and having higher job satisfaction than their less gritty counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This finding aligns with others works that have demonstrated how human flourishing occurs when habits are persistently regulated to be in congruence with self-transcendent goals and values, thus resulting in a well-integrated personality 62 . Other constructs related to motivational persistence and perseverance, such as grit , have also been consistently associated with positive emotional experiences 84 .…”
Section: Discussionmentioning
confidence: 99%
“…Grit has also been found to be relevant to job performance ( Ion et al, 2017 ; Mueller et al, 2017 ) and teacher effectiveness ( Robertson-Kraft and Duckworth, 2014 ). In their meta-analysis with 83 studies involving 66,518 participants, Hou et al (2021) has revealed the positive relation of grit with subjective well-being.…”
Section: Literature Reviewmentioning
confidence: 99%